The net economic benefits from eradication of invasive alien vegetation: The case of the Inkomati Catchment Mpumalanga Province in South Africa - Hassan, Rashid M. (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2018.